PENGARUH STRUKTUR KEPEMILIKAN SAHAM TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - -, Ratnawati - (Magister Manajemen Universitas Wisnuwardhana, 2015)
Abstract: The purpose of this study was to examine the effect of managerial stock ownership, institutional and foreign to the disclosure of CSR. The population of this study is a manufacturing company that went public in the Indonesia Stock Exchange for the year 2012 totaling 131 companies. The samples used purposive sampling approach dengen Judgment Sampling generate a total sample of 55 companies. The results showed that managerial stock ownership negatively affect the disclosure of corporate social responsibility. Institutional share ownership has a positive effect on corporate social responsibility. Foreign ownership has no effect on corporate social responsibility. Keywords: managerial shareholding, institutional shareholding, foreign ownership and corporate social responsibility disclosure